Penerapan E-Commerce sebagai Strategi Peningkatan Penjualan Produk pada PT Daehsan Indonesia : Cabang Medan - Siska Ade Putry; Furqan Khalidy (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
, it has driven very significant changes to the marketing and sales strategies of various companies in the business sector. One of the influential innovations is the implementation of e-commerce (electronic commerce), which allows the buying and selling transaction process to be carried out online through the internet network. E-commerce is not only a means to sell products, but it also plays an important role in expanding market reach, increasing the effectiveness of promotions, and strengthening the relationship between companies and consumers. This study aims to analyze the application of e-commerce as a strategy to increase product sales at PT Daehsan Indonesia Medan Branch. The research method used is qualitative descriptive with data collection techniques through interviews, observations, and documentation of management and distributors involved in the company's digital marketing activities. In addition, this study also reviews the supporting factors and obstacles that arise during the implementation of e-commerce, so that it can provide a comprehensive picture of the extent to which the use of digital platforms affects the increase in sales volume, the expansion of market reach, and the level of customer satisfaction.